Analisis Ekspresif Lagu Teramini Karya Ghea Indrawari: Pendekatan Pragmatik - Nanda Astria (Literasi: Jurnal Pendidikan Guru Indonesia, 2024)
Research conducted on the lyrics of the song Teramini by Ghea Indrawari, which was published on March 10 2024, aims to understand the deeper meaning by using expressive analysis in pragmatic studies. In this research, qualitative descriptive methods were used as research methods. Data and data sources are the lyrics of the song Teramini. The research collected data using the listening and note-taking method. The researcher recorded every illocutionary speech act in the song lyrics which would be explained after the writer listened to the lyrics. The data analysis used is document analysis. By looking at the illocutionary speech acts used by Ghea Indrawari in the song Teramini, it is hoped that readers or listeners can better understand the meaning, message and feelings felt by the creator of this song. The research results show that there are several types of illocutionary speech acts, namely assertive or representative, directive, expressive and commissive.